P217 Improving care and support in advanced copd – six recommendations from the population-based living with breathlessness study. (15th November 2016) - Farquhar, MC; Ewing, G; White, P; Burge, P; Mahadeva, R; Gardener, AC; Moore, C; Howson, S; Booth, S; Saunders, C; Ling, T
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is a chronic life-limiting condition with high symptom-burden and carer-burden. National guidance on end of life care calls for quality care for patients with any condition, yet we rely on frameworks developed for cancer with its largely predictable trajectory. Aim: To develop evidence-based recommendations to inform a new framework to improve care and support of patients living with advanced COPD and their informal carers. Methods: The Living with Breathlessness Study was a multiple-component, population-based, mixed-method longitudinal, multiple-perspective research programme to identify new evidence on health and social care needs and preferences of patients with advanced COPD and their carers. It followed more than 500 patients and carers for up to 18-months through interview and survey methods. Qualitative data on barriers and facilitators to meeting needs were collected from clinicians. Programme-wide evidence was synthesised to identify recommendations. Stakeholder views were then collected through a workshop and online survey. Results: Six inter-related recommendations emerged, linked by the concept of proactive person-centred care: (1) Stop the continual focus on the challenge of prognosis and unpredictability of trajectories as barriers to meeting needs, (2) Change targets to incentivise person-centred care within existing services, (3) Enable identification and response to patient support needs (through evidence-based tools and approaches), (4) Identify and support patients' informal carers (through evidence-based tools and approaches), (5) Identify and respond to psychological morbidity in patients and informal carers identify and respond to psychological morbidity, (6) Change societal attitudes and understandings of COPD, breathlessness, palliative care and informal carer support. The recommendations are underpinned by action points to enable delivery. The recommendations garnered significant support from stakeholders, with caution regarding ease of implementation which varied by recommendation. Conclusion: These six inter-related recommendations, and supporting action points, could inform a new framework for care and support in advanced COPD likely to have resonance for those living with other advanced non-malignant long term conditions, and for clinicians striving to support them.